Analysis of Anthroponymic Vocabulary in Armenian - DILBARYAN, NARINE (Bulletin of Yerevan University B: Philology, 2021)
Proper names like common nouns have their general lexical characteristics. The anthroponymic vocabulary of the language consists of two major layers: a) active names or basic anthroponymic vocabulary and b) passive names. The second layer in its turn has 2 subgroups: 1) obsolete names and 2) new names, neologisms, which are not rooted in the active anthroponymic vocabulary. These names can easily be transferred in the course of time into the active layer or become occasionally In the musoedde rwno ardn tuhnroitpso. nymic vocabulary of the Armenian literary language, we would note the following main tendencies are noted in the selection and use of personal names: a) complex or composite anthroponyms are replaced with shorter ones, compound names lose their suffixes or other root particles thus becoming short monosyllabic names, for example, Արեգնազ (Aregnaz) > Արեգ (Areg), Ոսկեհատ (Voskehat)> Ոսկի (Voski), Նաիրուհի (Nairuhi) > Նաիրի (Nairi), Արևիկ (Arevik) > Արեւ(Arev), Աստղիկ (Astghik) > Աստղ (Astgh), b) the increasing use of so-called universal, common names, which are both female and male anthroponyms: Արեգ (Areg), Տաթև (Tatev), Նաիրի (Nairi), Վան (Van), Շուշի (Shushi), c) the most popular foreign names, mainly European and biblical, national names are used less, names of this type are losing their function of national identification – Էլեն (Elen), Միլենա (Milena), Ալան (Alan), էրիկ (Erik), Էդուարդ (Eduard), Ալեքս (Alex), Մարիա (Maria), Մերի(Meri), Մարի (Mari), Էմանուել (Emanuel), Սառա (Sara), Եվա (Eva) etc. The latest tendency is quite alarming.